Response of Dunaliella salina Teod. culture to various regimes of fed-batch nutrient supplementation - Komaristaya, V.P.; Antonenko, S.P.; Rudas, A.N. (Харківський національний аграрний університет, 2016)
There were studied D. salina culture growth, beta-carotene and total protein accumulation under various fed-batch regimes: supplementation of nitrate and phosphate, nitrate or phosphate solely, and after the switch of nitrate supplied culture to phosphate supplementation and vice versa. Pre-cultures, unsupplied with the both or any nutrient, accumulated beta-carotene. The sub-cultures supplied in turns with nitrogen and phosphorus, thus surviving one or the other nutrient depletion, regained culture growth ability, lost the ability to accumulate beta-carotene and started to accumulate protein. The ability to reserve the available nutrient under another nutrient deficiency was hypothesized as D. salina possible ecological strategy, including assimilated carbon storage in triacylglycerides (TAGs) and beta-carotene accumulation to prevent TAGs oxidation. The outcomes for industrial D. salina culture are discussed.
Keywords: Dunaliella salina; nitrate; phosphate; beta-carotene; total protein